Forecasting Information System with Single Exponential Smoothing Method in Pharmaceutical Companies PT. Priest Nirmala/Fahrenheit - Nunung Nurmaesah; Rosana Junita Sirait; Anirotul Hikmah (Institut Teknologi dan Bisnis Bina Sarana Global, 2022)
Forecasting systems play an important role in business and economics. In the planning of drug production at PT. Pratapa Nirmala is still semi-computerized, which is limited to recording using the Microsoft Excel program and has not used definite methods or tools, thus allowing for human errors and significant differences between forecasting and actual sales which will affect stock out and over-stock drug supplies. Forecasting is a calculation analysis technique that is carried out with qualitative and quantitative approaches to predict future events using data from the past. The method used is observation, interview, and research, and the type of research used is quantitative and qualitative with descriptive analysis. This system uses an object-oriented design method with UML (Unified Modeling Language). The programming language used is the PHP programming language with MySQL database and the forecasting method used is Single Exponential Smoothing by considering the Mean Absolute Percentage Error (MAPE) value. After the calculation, obtained with an alpha value of 0.9, where the value of the Mean Absolute Percentage Error generated is 16%. and the form of the forecasting equation model is Ft = Ft-1 + a (At-1 – Ft-1). So this forecast is feasible and can be applied.